Research, challenges and opportunities in software define radio technologies - Jacob Abraham; Kanagaraj Venusamy; Antony Judice; Joel Livin A. Obtained; Hameed Shaik; Kannadhasan Suriyan (International Journal of Reconfigurable and Embedded Systems (IJRES), 2023)
The network extended not just internationally but also throughout a broad variety of application areas in this age, with healthcare being one of the most well-known and vital industries. Improvements in healthcare are possible if we start using the popular internet of things (IoT) technology as a key instead of focusing on other disciplines. Wireless body area network (WBAN) is a field in which we communicate with a network of human people and medical equipment that may be used in conjunction with internet of things technology to perform any function. Additional features for software defined networks will be added in the future. In the event of a critical crisis, the suggested suggestions will be to take care of the patient's life. Because the fitted equipment keeps a lot better eye on the patient than previously advised methods. This study combines WBAN, IoT, and software defined network (SDN) to make sense in the healthcare field.